2022
DOI: 10.3390/nano12213918
|View full text |Cite
|
Sign up to set email alerts
|

Co-Treatment of Caco-2 Cells with Doxorubicin and Gold Nanoparticles Produced from Cyclopia intermedia Extracts or Mangiferin Enhances Drug Effects

Abstract: Mangiferin (MGF) is a natural and valuable polyphenol found in significant levels in many plant species, including Cyclopia intermedia (C. intermedia). In a previous study, we synthesized gold nanoparticles (AuNPs) using MGF and a water extract of C. intermedia and reported that these AuNPs have very low cytotoxicity toward a human colon cancer (Caco-2) cell line. Although the study also showed that these biogenic AuNPs in combination with doxorubic (DOX) significantly augmented the cytotoxic effects of DOX in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The drug-sensitizing effects of AuNPs are currently being explored in the fight against cancer to enhance chemotherapeutic drug efficacy while reducing their side effects. Previous studies have demonstrated that co-administration of plant-mediated AuNPs and Dox has the potential to enhance the anti-cancer effects of Dox [6,53]. Of interest, unlike other studies, HB-AuNPs_ci were able to augment the cytotoxicity of Dox when used at a very low and non-toxic dose [4].…”
Section: Internalization Of Hb-aunpsmentioning
confidence: 97%
See 4 more Smart Citations
“…The drug-sensitizing effects of AuNPs are currently being explored in the fight against cancer to enhance chemotherapeutic drug efficacy while reducing their side effects. Previous studies have demonstrated that co-administration of plant-mediated AuNPs and Dox has the potential to enhance the anti-cancer effects of Dox [6,53]. Of interest, unlike other studies, HB-AuNPs_ci were able to augment the cytotoxicity of Dox when used at a very low and non-toxic dose [4].…”
Section: Internalization Of Hb-aunpsmentioning
confidence: 97%
“…The number of studies describing the use of plant-mediated NPs has increased significantly in the past decade, as well as research describing the possible health benefits of these biogenic NPs in pre-clinical [4,31,35] and clinical studies [28]. As a follow-up to our previous studies [4,6], in the current study we investigated the effect of HB-AuNPs synthesized from C. genistoides on cancer cells either alone or in combination with Dox. Phytochemicals in the HBE served as reducing and capping agents in the synthesis of stable and bioactive HB-AuNPs following optimization of temperature, HBE concentration, and time of synthesis.…”
Section: Synthesis and Characterization Of Hb-aunpsmentioning
confidence: 99%
See 3 more Smart Citations